Model Pemilihan Angkutan Sekolah : Studi Kasus Kawasan Kotabaru, Yogyakarta - Antonius Haryo I (Faculty of Engineering, Universitas Gadjah Mada, 2003)
)Alumni Jurusan Teknik Sipil Fakultas Teknik UGMSigit PriyantoJurusan Teknik Sipil & Magister Sistem dan Teknik Transportasi UGMAbstractWith it's title as a city of student, Yogtakarta has a large amount of students which isaround 105,684 students, Iiving in Yogtakarta city. Therefore, it was concluded that trafic inYogtakarta could be much influenced by students. The intention of this research is tounderstand the characteristics of students traveling with private cars, and if they are offeredpublic transportation and they choose it. Therefore the congestion can be reduced.The stated preference method is applied to this study to investigate the response of privatecar passengers to shift in public transportation in school troveling.The results showe that if the public transport is available they may be choose it rather thanprivate cars.Keywords: public transport, private car, school traveling